PENGARUH DANA PERIMBANGAN TERHADAP TINGKAT KEMANDIRIAN KEUANGAN KABUPATEN/KOTA DI PROVINSI MALUKU - Falia, Febby Tri; Masnila, Nelly; Sarikadarwati (Jurnal Riset Terapan Akuntansi, 2025)
This study was conducted to examine the influence of General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund on the Level of Financial Independence in local governments in 11 regen-cies/cities in Maluku Province during the 2019-2023 period, with a total of 55 observations. This study used a quantitative approach with multiple linear regression analysis methods and classical assumption tests using the SPSS version 25 program. The results showed that simultaneously DAU, DAK, and DBH significantly influenced the Level of Financial Independence. Partially, DAU had a significant positive effect, DAK had a significant negative effect, while DBH had no significant effect on Financial Independ-ence. This finding strengthens the agency theory in the context of regional financial management, where local governments as agents are expected to be able to manage transfer funds efficiently to increase fiscal independence. The policy implication of this study is the need to optimize the utilization of balancing funds, especially DAK, for productive activities that can encourage an increase in Regional Original In-come (PAD) and reduce fiscal dependence on the central government. Keywords: General Allocation Funds, Special Allocation Funds, Revenue Sharing Funds, Level of Finacial Independence.